A sensitive photoluminescent chemosensor for cyanide in water based on a zinc coordination polymer bearing ditert-butyl-bipyridine. Issue 33 (10th July 2019) - Rosales-Vázquez, Luis D.; Valdes-García, Josue; Bazany-Rodríguez, Iván J.; Germán-Acacio, Juan M.; Martínez-Otero, Diego; Vilchis-Néstor, Alfredo R.; Morales-Luckie, Raúl; Sánchez-Mendieta, Víctor; Dorazco-González, Alejandro
Abstract : Sensitive and direct sensing of cyanide in buffered aqueous solutions at pH = 7.0 by three new blue photoluminescent zinc-1, 4-cyclohexanedicarboxylato coordination polymers bearing di-alkyl-2, 2′-bipyridines has been achieved. Abstract : Sensitive and direct sensing of cyanide in buffered aqueous solutions at pH = 7.0 by three new blue photoluminescent zinc-1, 4-cyclohexanedicarboxylato coordination polymers bearing di-alkyl-2, 2′-bipyridines has been achieved. Specifically, a Zn-polymer with the general formula: [Zn2 (H2 O)2 ( e, a-cis -1, 4-chdc)2 (4, 4′-dtbb)2 ]·7H2 O n, (1, 4-chdc = 1, 4-cyclohexanedicarboxylato and 4, 4′-dtbb = 4, 4′-ditert-butyl-2, 2′-bipyridine) has been synthesized in high yield and studied as a luminescent chemosensor for halides, pseudohalides and a series of oxyanions in neutral water. CN − ions can be quantitatively detected by this polymer based on complete quenching ( λ em = 434 nm) in the sub-micromolar concentration range with a pronounced selectivity over common anions such as acetate, bromide and iodide. The quenching response ( K SV = 9.7(±0.2) × 10 4 M −1 ) by the addition of CN − was also observed in the presence of typical interfering anions with a very low detection limit of 0.9 μmol L −1 in buffered water at pH = 7.0. On the basis of the crystal structure and solid state CPMAS 13 C-NMR correlation and 1 H NMR, IR-ATR, MS-ESI(+) and SEM-EDS experiments, the optical change is attributed to the efficient release of its corresponding ditert-butyl-bipyridine, with the simultaneous formation of a zinc cyanide complex. The CPMAS 13 C-NMR spectrum of the coordination polymer is consistent with the symmetry of the crystal structure. The use of flexible coordination polymers as fluorescent sensors for fast and selective detection of cyanide ions in pure aqueous solutions has been unexplored until now.